GRB Numerical Chemistry For JEE (Main & Advanced) - Bahadur Dr. P. (G.R. Bathla Publications Pvt. Ltd, 2025)
GRB Numerical Chemistry for JEE (Main & Advanced), 25th Edition by Dr. P. Bahadur is a comprehensive guide tailored for aspirants of engineering entrance exams like JEE Main and Advanced. It offers a wide array of practice questions and detailed explanations, making it a valuable resource for mastering physical chemistry topics. The book is well-regarded for its clarity and depth, serving as a trusted companion for serious JEE candidates.